2012
DOI: 10.1021/cg201604z
|View full text |Cite
|
Sign up to set email alerts
|

A Common Regularity of Stoichiometry-Induced Morphology Evolution of Transition Metal Carbides, Nitrides, and Diborides during Self-Propagating High-Temperature Synthesis

Abstract: The morphologies of the transition metal carbide (TMC) (ZrC x , NbC x , and TaC x ), transition metal nitride (TMN) (TiN x ), and transition metal diboride (TMD) (NbB 2x and TaB 2x ) particles formed during the selfpropagating high-temperature synthesis (SHS) were investigated. The results indicate that the ceramics with wide stoichiometric ranges all show a stoichiometry-induced morphology evolution, i.e., octahedron → truncated-octahedron → spherelike → sphere, for TMCs and TMNs, and hexagonal prism → polyhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 87 publications
2
26
0
Order By: Relevance
“…It is still urgently desired to develop a straightforward and environmentfriendly technique for industrial manufacturing of high-quality carbon materials directly form CO 2 . Since the pioneering work of Merzhanov et al [136] in 1960s, a self-sustaining reaction called self-propagating high-temperature synthesis (SHS) has received much attention from both academia and industry as a novel protocol to manufacture useful ceramics [137,138], intermetallics [139], refractory materials [138], and thermoelectric materials [140,141]. The foremost feature of SHS technique is an essentially exothermic reaction ignited by a small amount of energy input to one part of the system, then the released heat is sufficient to generate a combustion wave that spontaneously propagates in a self-sustaining manner throughout the remaining parts of the reaction system.…”
Section: Controllable Self-sustaining Reaction With Comentioning
confidence: 99%
“…It is still urgently desired to develop a straightforward and environmentfriendly technique for industrial manufacturing of high-quality carbon materials directly form CO 2 . Since the pioneering work of Merzhanov et al [136] in 1960s, a self-sustaining reaction called self-propagating high-temperature synthesis (SHS) has received much attention from both academia and industry as a novel protocol to manufacture useful ceramics [137,138], intermetallics [139], refractory materials [138], and thermoelectric materials [140,141]. The foremost feature of SHS technique is an essentially exothermic reaction ignited by a small amount of energy input to one part of the system, then the released heat is sufficient to generate a combustion wave that spontaneously propagates in a self-sustaining manner throughout the remaining parts of the reaction system.…”
Section: Controllable Self-sustaining Reaction With Comentioning
confidence: 99%
“…Jin et al found a temperature-related growth behavior in the Al-Ti-C reaction system during the self-propagating high-temperature synthesis process, and they demonstrated that the TiC x particles transformed from octahedrons and truncated octahedrons to spheres upon increasing the temperature [13]. Their later studies illustrated that the intrinsic morphology evolution of TiC crystal was caused by the induction of stoichiometric ratio [30,85,86]. The corresponding evolutions are shown in Figure 10d.…”
Section: The Synthesis and Characterization Of Three-dimensional Tmentioning
confidence: 99%
“…It isinexpensive and has good stability, while its average size is relatively large. In previous studies, graphite particles of approximately 5 μm, 15 μm, 38 μm or even 48 μm were reported as used to fabricate TiC [30,75,80,86]. Becasuse graphite has a large size, it always becomes a residual phase in the reactant and has not been completely reacted with Ti, except for via some special measures [81].…”
Section: The Synthesis and Characterization Of Three-dimensional Tmentioning
confidence: 99%
See 1 more Smart Citation
“…3,11,12 In literature, it has been reported that the different morphologies of TiC such as octahedron, cubic, hexagonal, and spherical can be achieved, based on the temperature of SHS. [13][14][15] However, as far as we know, no basic study regarding the reasons for these observations was reported, until the valuable studies of Jin et al 13,16,17 In their works, the morphological evolution of the TiC particles as a function of the reaction temperature was reported. With decreasing the reaction temperature during SHS, the shape of TiC particles changed from a spherical shape to an octahedron one.…”
Section: Introductionmentioning
confidence: 99%